Milan Svoboda – The Man in Background - Pokorný Vít (Slovenské divadlo)
The study represents the life and artistic career of today’s almost forgotten theatre director Milan Svoboda (1883 – 1948). It is based on the extensive Svoboda estate, located in the Theatre Department of the National Museum. It follows the artist from his amateur beginnings in Roudnice nad Labem, through his career as a pedagogue at the Prague Conservatory, theatre director at the Slovak National Theatre, guest director at the National Theatre in Prague, to his post-war effort to create high-quality stage art in the border villages abandoned by the Germans. Thanks to the substantial and rich material found in his estate, the study demonstrates the conflict of creative ideals and the desire to seek an aesthetic beauty in a world within a regimented state, grand political scheming, critics and “progressive” theatrical colleagues.